SOLVING PROBLEMS ON THE TEACHING METHODS OF LINEAR ALGEBRA THROUGH TECHNOLOGY PLATFORM DOT.NET - Iskakova, Makpal; Adilbekov, Yernar (European Scientific Journal, ESJ, 2013)
This article will be considered when solving problems on linear algebra. It present a method in solving this problem with the use of computer technology, and also presents a list of tasks to be solved with various applications that was created on platform DOT.NET. This application is quick and easy to understand and will help everyone to understand linear algebra.